Recent research progress on the correlation between metabolic syndrome and Helicobacter pylori infection - Xie, Qinli; He, Yangjun; Zhou, Danni; Jiang, Yi; Deng, Ying; Li, Ruoqing (PeerJ, 2023)
Background Globally, metabolic syndrome (MS) and Helicobacter pylori (HP) infection, which have gained an epidemic status, are major challenges to human health, society, and medical professionals. Recent studies have demonstrated that MS is closely related to HP infection. Additionally, HP is an important risk factor for gastric cancer. However, systematic reviews on HP are lacking. This review aimed to summarize and analyze the potential correlation of HP infection with MS and its components, as well as the underlying mechanism, to provide reference and strategies for clinical prevention and treatment. Methodology Previous studies examining the correlation between HP and MS since 1990 were retrieved from the PubMed, Web of Science, and Embase databases. The potential correlation between HP infection and MS and its components was comprehensively analyzed. The keywords “Helicobacter pylori,” “HP,” “metabolic syndrome,” “hypertension,” “obesity,” “diabetes,” or “dyslipidemia” were used in all fields. No language restrictions were imposed. Results MS was strongly correlated to HP infection. The inflammatory response and inflammatory factors produced during HP infection are important etiological factors for insulin resistance and MS. The co-occurrence of long-term chronic inflammation and immune dysfunction with MS may be the predisposing factor for HP infection. MS components, such as diabetes, hypertension, dyslipidemia, and obesity were also correlated with HP infection in one or both directions. Conclusions HP infection and MS may promote the pathogenesis of each other. The contribution of HP infection and MS to gastric cancer cannot be ruled out based on co-occurrence. The MS components diabetes and obesity may be bidirectionally correlated with HP infection.
Keywords: Metabolic syndrome; Helicobacter pylori; Insulin resistance; Inflammatory factors